Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 3)
"Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 3)" [g0973003.jpg], n.d.